PPh Pasal 22 dan PPh Pasal 23 - Leni Shofiyani; Mutia Salwa Hutahuruk; Servina Rahayu (STIKes Ibnu Sina Ajibarang, 2024)
The aim of research into income tax articles 22 and 23 is to understand and analyze the financial and fiscal implications of the law on individuals and society as a whole. This research can cover various aspects, such as export and import activities, sales of production results, and how to calculate PPh Article 22 and PPh Article 23. Income Tax Article 22 is the payment of Income Tax in the current year which is collected by the government treasurer, certain agencies and Certain corporate taxpayers. Income Tax Article 23 According to Law Number 36 of 2008 is tax withheld on income received or earned by domestic taxpayers. This research can help identify weaknesses or inconsistencies in the tax system, which can lead to improvements and increased effectiveness. As well as identifying ways to increase community involvement in the tax decision-making process, which can lead to more inclusive and fair tax policies.